2021
DOI: 10.11646/zootaxa.5036.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Illustrated key to the genera and catalogue of Mymaridae (Hymenoptera) in the Afrotropical region

Abstract: Separate identification keys for females, and for males where known, of the 40 genera of Mymaridae (Hymenoptera: Chalcidoidea) in the Afrotropical region are given. The subgenera of four genera are also included in the key to females. The genera are illustrated with over 300 photographs. The 122 named, valid species reported from the region are catalogued. Reliable host records are reported for 6 genera and 11 species from rearings undertaken in the region. An appendix lists the 27 species from northern Africa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Anwar et al (2020) reported that it is an undetermined male of Eofoersteria Mathot based on four segmented tarsi. Huber et al (2021) synonymised Eofoersteria under Camptoptera and explained that loss of one funicle segment in females, and reduction of tarsal number due to fusion of the apical two segments were sufficient to keep it as a subgenus, but all other features place Eofoersteria in Camptoptera. At present following Huber et al (2021) we have placed the recorded species of Eofoersteria under the subgenus of Camptoptera and provided their brief diagnoses with illustrations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Anwar et al (2020) reported that it is an undetermined male of Eofoersteria Mathot based on four segmented tarsi. Huber et al (2021) synonymised Eofoersteria under Camptoptera and explained that loss of one funicle segment in females, and reduction of tarsal number due to fusion of the apical two segments were sufficient to keep it as a subgenus, but all other features place Eofoersteria in Camptoptera. At present following Huber et al (2021) we have placed the recorded species of Eofoersteria under the subgenus of Camptoptera and provided their brief diagnoses with illustrations.…”
Section: Discussionmentioning
confidence: 99%
“…Huber et al (2021) synonymised Eofoersteria under Camptoptera and explained that loss of one funicle segment in females, and reduction of tarsal number due to fusion of the apical two segments were sufficient to keep it as a subgenus, but all other features place Eofoersteria in Camptoptera. At present following Huber et al (2021) we have placed the recorded species of Eofoersteria under the subgenus of Camptoptera and provided their brief diagnoses with illustrations. Classification of Camptoptera is still unresolved and we strongly believe that an informal species-group placement would be rather useful to identify genus upto species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…from New Zealand (Huber 2017) with an ovipositor over twice that length when extended. In the Nearctic and Neotropical regions, the longest species belong to Acmopolynema varium Girault at 2500 µm (Huber et al 2020) and Megamymar waorani Huber at 4800 µm (Huber & Read 2022), respectively. The largest Oriental species (in an undescribed genus) is about 2800 µm in length.…”
Section: Intraspecific Variationmentioning
confidence: 99%
“…More recently, Anwar et al (2021a) added three species of the genus from India (described one and recorded two known Taiwanese species). Huber et al (2021) synonymised the genus Eofoersteria Mathot (1966) under Camptoptera and treated it as a subgenus of Camptoptera and Anwar et al (2021b) provided the first ever description of the males of Camptoptera (Eofoersteria). The genus presently contains 33 species from Oriental region and 30 species from India (including two species described here as new) which makes it most diverse regions of the world in terms of Camptoptera species.…”
Section: Introductionmentioning
confidence: 99%